Management of Hypertensive Crisis Emergencies in Primary Healthcare Facilities: Challenges and Solutions - Syah, Rahmad (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Hypertension crisis is a medical emergency that requires immediate treatment to prevent serious complications, such as stroke and heart failure. Primary healthcare facilities have an important role in early detection and early treatment of crisis hypertension, but still face various challenges in its implementation. Objectives: This study aims to analyze the challenges in the management of hypertensive crisis emergencies in primary healthcare facilities and identify solutions that can be implemented to improve the effectiveness of services. Methods: This study used a descriptive qualitative approach with in-depth interviews with medical personnel in primary healthcare facilities. In addition, an analysis of current policies and direct observation of the availability of drugs and medical devices that support the management of hypertension crisis were conducted. Results: The results showed that the main challenges in the management of hypertension crisis include the lack of training of medical personnel, limited availability of emergency antihypertensive drugs, and an unoptimal referral system. Lack of patient awareness of the symptoms of hypertensive crisis is also a contributing factor to the delay in treatment. Conclusion: To overcome these challenges, strategies are needed that include periodic training for medical personnel, improving the distribution and availability of drugs in primary health facilities, and optimizing the referral system.